Fabrication of defects in 3D printed materials for ultrasonic analysis - Sim, Royston Wen Kang (Nanyang Technological University, 2023)
This research is part of a multi-year project that aims to advance 3-D printing technology and its applications across various industries. Over the past 5 years, the project has used Non-Destructive Testing (NDT) technology to test the boundaries of 3-D metal printing and has had great success. This study then further explores the capabilities of using NDT to identify and locate defects in 3-D printed polylactic acid (PLA) specimens. PLA is the most common plastic material used in commercial 3-D printing sphere which merits the research, however it is known to be a highly attenuative material which poses as a significant challenge to the project. This project focuses on two key areas: the examination of the ability and accuracy of using different Ultrasonic Testing (UT) techniques on PLA material, and the study and detailing of procedures for testing highly attenuative materials. Industry interviews and visits were conducted with experts from both the 3-D and NDT industries to understand the different viewpoints and pain points they had respectively. An embedded defect was then carefully designed using SolidWorks and fabricated using Fused Deposition Modelling (FDM) technology. A-Scan which uses UT was then used to understand FDM technology, and also to locate and define the fabricated defects. A second specimen was then designed to mimic “real” defects. This report shows the ability of UT to test PLA materials, with the build and experimental procedures carefully detailed. Recommendations for future studies and further analysis have been included in this paper.